Construction of CoS/Cd0.5Zn0.5S ohmic heterojunctions for improving photocatalytic hydrogen production activity. (6th December 2022) - Jiang, Shuhan; Shen, Luping; Liu, Yanan; Qi, Shuaikang; Lu, Zhufeng; Li, Lei; Ma, Hongxia; Wang, Hongmei
Abstract : The optimized CoS/Cd0.5 Zn0.5 S ohmic heterojunction showed excellent stability over four cycles and its hydrogen evolution rate reached 6916.7 μmol g −1 h −1 . Abstract : CoS/Cd0.5 Zn0.5 S ohmic heterojunctions were successfully constructed by a two-step solvothermal method. The CoS/Cd0.5 Zn0.5 S heterojunctions were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance spectroscopy (UV-vis) and ultraviolet photoelectron spectroscopy (UPS). The introduction of CoS can effectively improve the photocatalytic hydrogen evolution activity of Cd0.5 Zn0.5 S, and its content has an impact on the activity of the CoS/Cd0.5 Zn0.5 S heterojunction. The hydrogen evolution rate of the 30%-CoS/Cd0.5 Zn0.5 S nanocomposite reached 6916.7 μmol g −1 h −1 in 3 vol% lactic acid aqueous solution with an optimal quantum efficiency of 9.32%, which is 5.1 times that of pure Cd0.5 Zn0.5 S. Moreover, the 30%-CoS/Cd0.5 Zn0.5 S sample shows good photocatalytic hydrogen production stability. Mechanistic studies suggest that CoS/Cd0.5 Zn0.5 S with an ohmic heterojunction can effectively transfer and separate the photogenerated electrons and holes, thereby improving the photocatalytic hydrogen production. This work could offer a facile and low-cost strategy for the construction of composite photocatalysts with high-efficiency hydrogen evolution.